Â€˜UNICHECKINGÂ€™: FACT-CHECKING PROJECT DURING THE 2022 BRAZILIAN GENERAL ELECTIONS (CIPEEX, 2022)
THE UNICHECKING PROJECT WAS CARRIED OUT IN PARTNERSHIP WITH THE ORDER OF ATTORNEYS OF BRAZIL - GOIS SECTION (OAB - GO), THROUGH ITS SPECIAL COMMISSION AGAINST DISINFORMATION AND ELECTORAL CORRUPTION, AND ITS MISSION WAS TO ASSIST VOTERS BY VERIFYING THE VERACITY OF THE NEWS BROADCAST AND SHARED REGARDING THE POLITICAL ACTORS OF THE 2022 BRAZILIAN GENERAL ELECTIONS. WE PUT TOGETHER A TEAM OF STUDENTS FROM THE JOURNALISM, SOCIAL COMMUNICATION - ADVERTISING AND MARKETING, LAW AND INTERNATIONAL RELATIONS PROGRAMS AT THE EVANGELICAL UNIVERSITY OF GOIS, UNDER THE SUPERVISION OF PROFESSORS TO WORK IN THE VERIFICATION AND FACT-CHECKING OF NEWS SHARED ON DIFFERENT CHANNELS ABOUT THE ELECTORAL PROCESS. FOR EFFECTIVE FACT-CHECKING, OUR METHOD WAS STRUCTURED AS FOLLOWS: THE STUDENTS WERE ORGANIZED INTO THEMATIC AXIS RELATED TO THEIR TRAINING. UPON RECEIVING THE REPORTS SUBMITTED DIRECTLY TO A HOTLINE PROVIDED BY THE OAB-GO THE DETAILING AND VERIFICATION OF THE NEWS WAS MADE. SOON AFTER, THEY RECEIVED THE FOLLOWING SEALS: 1. FALSE; 2. TRUE; 3. NO DATA; AND 4. INACCURATE. THE SEAL IS ACCOMPANIED BY AN EXPLANATORY TEXT. WE CONCLUDE THAT THE ACTIVITY WAS AN EXCELLENT PRACTICAL AND TRANSDISCIPLINARY EXERCISE AND IT IS ESSENTIAL THAT THE UNIVERSITY, WHOSE MISSION INCLUDES THE DEVELOPMENT OF INDIVIDUALS COMMITTED TO THE TRUTH, COLLABORATE IN ORDER TO BUILD A RELIABLE, IMPARTIAL AND FAIR ENVIRONMENT FOR CONDUCTING THE ELECTORAL PROCESS.
Keywords: Fact-checking; Fake News; 2022 Elections